Strength training improves running economy durability and fatigued high-intensity performance in well-trained male runners: A randomized control trial - Zanini, M.; Folland, J. P.; Wu, H.; Blagrove, R. C. (Medicine & Science in Sports & Exercise, 2025)
Introduction Strength training improves running economy (RE) in a nonfatigued state and performance after prolonged exercise at moderate intensity. However, it is unknown if strength training improves RE durability at marathon race intensity, or high-intensity performance akin to the final stages of a competitive race. This study quantified the effect of a supplementary 10-wk strength training program on RE throughout 90 min of running in the heavy-intensity domain, and subsequent fatigued performance in runners.